2020
DOI: 10.1097/gox.0000000000003286
|View full text |Cite
|
Sign up to set email alerts
|

Deep Layer Radiofrequency Thermo-coagulative Technology for Cervicofacial Contouring: Sonographic and Clinical Results

Abstract: Background: Radiofrequency energy thermally induces collagen contraction and remodeling. The resultant dermal tightening is well established. However, facial aging encompasses also deeper layers of collagen-containing tissues. We present a deep layer radiofrequency-based thermo-coagulative technique for cervicofacial contouring and evaluate its efficacy. Methods: This prospective single center study was conducted from June 2017 to June 2018 and included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…All tissues are coagulated, including vessels, lymphatics, nerves, and connective tissue, causing the tissue to condense. 15,35 There is no evidence for a more delicate controlled action like strings on the dermis. 40 The liquefied tissue resembles a milkshake as it is aspirated.…”
Section: Comparison With Surgical Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…All tissues are coagulated, including vessels, lymphatics, nerves, and connective tissue, causing the tissue to condense. 15,35 There is no evidence for a more delicate controlled action like strings on the dermis. 40 The liquefied tissue resembles a milkshake as it is aspirated.…”
Section: Comparison With Surgical Resultsmentioning
confidence: 99%
“…2). Another study published almost simultaneously reported a prospective study of patients treated 26 Cohen et al 35 (2020) with the Thermi product. Major improvements in the jawline and neck were demonstrated in photographs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recalling that the total ability to re-drape the skin is related to the contractile nature of the dermis, as reflected by dermal thickness, the amount of FSN and fat to be aspirated, the delivery of RF energy to multiple tissue planes has proven advantageous. Treating the immediate subdermal layer leads to neo-collagenesis and subdermal remodeling, while treating above and below Scarpa's fascia maximally augments fat liquification, coagulates blood vessels, and creates an active fibroblastic reaction that replaces liquified fat [15,16], neo-angiogenesis, and a compact, reorganized layer of collagen and elastin over 4-6 months [17]. The delivery of immediate heating between 60 and 80°C causes collagen fibrils to contract to one third their length and alters the microenvironment of the extracellular matrix toward favorable remodeling and healing.…”
Section: Advantages Of Radiofrequency Energymentioning
confidence: 99%